An overview of the MATHILDA system - Kornerup, Peter; Shriver, Bruce D. (DAIMI Report Series, 1974)
A dynamically microprogrammable processor called MATHILDA is described. MATHILDA has been designed to be used as a tool in emulator and processor design research. It has a very general microinstruction sequencing scheme, sophisticated masking and shifting capability, high speed local storage, a 64-bit wide main data path, a horizontalty encoded microinstruction, and other facilities which make it reasonably well suited for this purpose. This paper presents an overview of the MATHILDA system.